Apolipoprotein CIII and diabetes. Is there a link?. Issue 3 (7th January 2019) - Christopoulou, Eliza; Tsimihodimos, Vasilios; Filippatos, Theodosios; Elisaf, Moses
Summary: Apolipoprotein CIII (ApoCIII), a small protein that resides on the surface of lipoprotein particles, is a key regulator of triglyceride metabolism. The inhibition of lipoprotein lipase (LPL), the increased assembly and secretion of very low‐density lipoproteins (VLDL) and the decreased reuptake of triglyceride‐rich lipoproteins (TRLs) by the liver are mechanisms associating elevated serum ApoCIII levels and hypertriglyceridemia. ApoCIII concentration is high in individuals with diabetes mellitus, indicating a possible positive correlation with impairment of glucose metabolism. The aim of this review (based on a Pubmed search until August 2018) is to present the possible mechanisms linking ApoCIII and deterioration of carbohydrate homeostasis. ApoCIII enhances pancreatic β‐cells apoptosis via an increase of the cytoplasmic Ca 2+ levels in the insulin‐producing cells. In addition, overexpression of ApoCIII enhances non‐alcoholic fatty liver disease and exacerbates inflammatory pathways in skeletal muscles, affecting insulin signalling and thereby inducing insulin resistance. Moreover, recent studies reveal a possible mechanism of body weight increase and glucose production through a potential ApoCIII‐induced LPL inhibition in the hypothalamus. Also, the presence of ApoCIII on the surface of high‐density lipoprotein particles is associated with impairment of their antiglycemic and atheroprotective properties. Modulating ApoCIII may be a potent therapeutic approach to manage hypertriglyceridemia and improve carbohydrate metabolism.